با استفاده از اتحاد مثلثاتی $\operatorname{Cos}2x={{\operatorname{Cos}}^{2}}x-{{\operatorname{Sin}}^{2}}x$، داریم:
$\frac{\operatorname{Cos}2x}{\operatorname{Sin}x+\operatorname{Cos}x}=\frac{{{\operatorname{Cos}}^{2}}x-{{\operatorname{Sin}}^{2}}x}{\operatorname{Sin}x+\operatorname{Cos}x}=\frac{(\operatorname{Cos}x-\operatorname{Sin}x)(\operatorname{Cos}x+\operatorname{Sin}x)}{\operatorname{Sin}x+\operatorname{Cos}x}=\operatorname{Cos}x-\operatorname{Sin}x=1$
همچنین با توجه به اتحاد مثلثاتی $\operatorname{Sin}x-\operatorname{Cos}x=\sqrt{2}\operatorname{Sin}(x-\frac{\pi }{4})$، داریم:
$\sqrt{2}\operatorname{Sin}(x-\frac{\pi }{4})=-1\Rightarrow (x-\frac{\pi }{4})=-\frac{\sqrt{2}}{2}=\operatorname{Sin}(-\frac{\pi }{4})$
$\left\{ _{x-\frac{\pi }{4}=2k\pi +(\pi +\frac{\pi }{4})\Rightarrow x=2k\pi +\frac{3\pi }{2}\xrightarrow{x\in \left[ 0,2\pi \right]}x=\frac{3\pi }{2}}^{x-\frac{\pi }{4}=2k\pi -\frac{\pi }{4}\Rightarrow x=2k\pi \xrightarrow{x\in \left[ 0,2\pi \right]}x=0,2\pi } \right.$
پس معادله در بازهی $\left[ 0,2\pi \right]$، سه جواب دارد.